Forebrain transcriptional response to transient changes in circulating androgens in a cichlid fish - Félix, Ana Sofia (2020)
It has been hypothesized that androgens respond to the social interactions as a way to adjust the behavior of individuals to the challenges of the social environment in an adaptive manner. Therefore, it is expected that transient changes in circulating androgen levels within physiological scope should impact the state of the brain network that regulates social behavior, which should translate into adaptive behavioral changes. Here, we examined the effect that a transient peak in androgen circulating levels, which mimics socially driven changes in androgen levels, has on the forebrain state, which harbors most nuclei of the social decision-making network. For this purpose, we successfully induced transient changes in circulating androgen levels in an African cichlid fish (Mozambique tilapia, Oreochromis mossambicus) commonly used as a model in behavioral neuroendocrinology by injecting 11-ketotestosterone or testosterone, and compared the forebrain transcriptome of these individuals to control fish injected with vehicle. Forebrain samples were collected 30 min and 60 min after injection and analyzed using RNAseq. Our results showed that a transient peak in 11-ketotestosterone drives more accentuated changes in forebrain transcriptome than testosterone, and that transcriptomic impact was greater at the 30 min than at the 60 min post-androgen administration. Several genes involved in the regulation of translation, steroid metabolism, ion channel membrane receptors, and genes involved in epigenetic mechanisms were differentially expressed after 11-ketotestosterone or testosterone injection. In summary, this study identified specific candidate genes that may regulate socially driven changes in behavioral flexibility mediated by androgens.